Burden and coping strategies of parents of children with attention deficit/ hyperactivity disorder in Hong Kong: A qualitative study - Wing Chi Wong; Irene Yuen Fung Wong (Wiley, 2021)
Abstract Aim Attention deficit/hyperactivity disorder is a prevalent mental disorder among children worldwide. The parents of children with ADHD experience great burden. However, burden and coping styles of these parents are seldom explored. The present study aimed to illustrate the burden and coping strategies of parents of children with Attention deficit/hyperactivity disorder. Design A descriptive qualitative study design was employed. Methods Samples were recruited from a general primary school in Hong Kong using convenience sampling. An information sheet was provided to participants, and written informed consent was obtained. Content analysis was conducted after the interviews were recorded and transcribed verbatim. COREQ reporting guidelines were used. Results Individual, face‐to‐face interviews were conducted, using a semi‐structured interview guide with 12 parents of children with attention deficit/hyperactivity disorder. Four themes (academic burden, children's social dependence, uncertainty regarding parenting strategies before diagnosis and emotional hardship) and three themes (acting according to situation, employing problemfocused coping methods and acceptance) emerged for burden and coping strategies, respectively. Coping strategies processes were also found. Medical diagnosis was reported to be a critical point for parents to shift their coping strategies. Timely interventions, such as early assessment and diagnosis, are recommended during or after medical diagnosis.